2022
DOI: 10.2340/17453674.2022.2744
|View full text |Cite
|
Sign up to set email alerts
|

Surgery rates for lumbar spinal stenosis in Denmark between 2002 and 2018: a registry-based study of 43,454 patients

Abstract: Background and purpose: Over the last decades, many countries have shown increased surgery rates for lumbar spinal stenosis (LSS), but little information is available from Denmark. We describe the development in diagnosis and surgery of LSS in Denmark between 2002 and 2018.Patients and methods: We collected diagnostic ICD10-codes and surgical procedure codes from private and public hospitals in Denmark from the Danish National Patient Register. Patients diagnosed with LSS and those with surgical procedure code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The continued increase in the use of decompression with fusion procedures in the US was unexpected and meaningful in the context of observed patterns among health care systems in other countries, such as those of Finland and Denmark, in which rates of decompression with fusion have either plateaued or declined substantially since 2016 . One of many possible explanations for this observation is that the findings from relevant RCTs, 2 of which were conducted in Europe, are not applicable to clinical practice, especially in a US patient population.…”
Section: Discussionmentioning
confidence: 98%
“…The continued increase in the use of decompression with fusion procedures in the US was unexpected and meaningful in the context of observed patterns among health care systems in other countries, such as those of Finland and Denmark, in which rates of decompression with fusion have either plateaued or declined substantially since 2016 . One of many possible explanations for this observation is that the findings from relevant RCTs, 2 of which were conducted in Europe, are not applicable to clinical practice, especially in a US patient population.…”
Section: Discussionmentioning
confidence: 98%
“…Symptomatic lumbar spinal canal stenosis is a debilitating condition and increasingly affects the aging population, with a mean prevalence upwards of 39% 1 . Surgical decompression, which is performed in approximately 30% of cases, 2 is considered the gold‐standard treatment for patients with symptomatic lumbar spinal stenosis who are refractory to conservative management 3 . However, in certain groups of patients, spine surgery may be associated with considerable morbidity and prolonged recovery 4–8 .…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Denmark from 2002 to 2018 examined surgery rates for LSS, revealing an overall annual surgery rate of 33% among diagnosed patients. During the study period, the rate of decompression without fusion increased by 128%, while the rate of decompression with fusion showed a larger increase of 199% [ 12 ]. Similarly, in the U.S., a study reported a 113% increase in lumbar fusion surgeries in 2001 compared to 1996 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%